2017
DOI: 10.14429/dlsj.2.12277
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of Iron oxide nanoparticles using Lagenaria siceraria and evaluation of its Antimicrobial activity

Abstract: Magnetic iron oxide nanoparticles (MNPs) with appropriate surface chemistry exhibit many interesting properties that can be exploited in a variety of biomedical applications such as magnetic resonance imaging contrast enhancement, tissue repair, hyperthermia, drug delivery and in cell separation. In this study unexplored Lagenaria siceraria leaves extract was found to be capable in green synthesis of Iron oxide nanoparticles (Fe 3 O 4 -NPs) and their characteristics were studied by using UV-visible spectrophot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 194 publications
(77 citation statements)
references
References 12 publications
3
74
0
Order By: Relevance
“…This means that the plant extracts will contain different concentrations of natural reducing agents which can influence the characteristics of the nanoparticles. Green synthesized iron oxide nanoparticles from plants offers an alternative for exploitation of plants for pharmaceutical, water treatment, biomedical and catalytic applications [13][14][15][16][17]. Previous studies have shown that iron nanoparticles produced from plants have been used to catalyze the degradation of organic dyes such as bromothymol blue, methylene blue, aniline and Rhodamine B [14,18].…”
Section: Introductionmentioning
confidence: 99%
“…This means that the plant extracts will contain different concentrations of natural reducing agents which can influence the characteristics of the nanoparticles. Green synthesized iron oxide nanoparticles from plants offers an alternative for exploitation of plants for pharmaceutical, water treatment, biomedical and catalytic applications [13][14][15][16][17]. Previous studies have shown that iron nanoparticles produced from plants have been used to catalyze the degradation of organic dyes such as bromothymol blue, methylene blue, aniline and Rhodamine B [14,18].…”
Section: Introductionmentioning
confidence: 99%
“…Green synthesis is currently under exploitation due to their eco‐friendly, safe, and cost‐effective approaches . It involves the selection of solvent medium, environmentally benign reducing agent, and the selection of nontoxic substances for the NPs synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…It involves the selection of solvent medium, environmentally benign reducing agent, and the selection of nontoxic substances for the NPs synthesis . One of the main challenges to prepare the MNPs avoiding the oxidation reaction during the synthesis process using seed, peel, and leaf extract . Moreover, green synthesis reduces the risk of further contamination by decreasing the reaction time and maintaining the crystal structure .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations